2015
DOI: 10.1111/dme.12758
|View full text |Cite
|
Sign up to set email alerts
|

Abnormalities in chromosome 6q24 as a cause of early‐onset, non‐obese, non‐autoimmune diabetes mellitus without history of neonatal diabetes

Abstract: Abnormalities in the imprinted locus on chromosome 6q24 do not necessarily cause transient neonatal diabetes. Non-penetrant 6q24-related diabetes could be an underestimated cause of early-onset, non-autoimmune diabetes in patients who are not obese and born small-for-gestational age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 15 publications
1
32
0
Order By: Relevance
“…Interestingly, some carrier relatives develop type 2 diabetes or gestational diabetes in adulthood without any evidence of having had NDM, as well as in a small fraction of patients with early‐onset, non‐obese, and non‐autoimmune diabetes without a history of NDM. This suggests significant variability in phenotype, possibly related to other genetic or epigenetic factors that may influence the clinical expression alterations of chromosome 6q24 …”
Section: Ndm Diabetes Diagnosed Within the First 6 To 12 Months Of Lifementioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, some carrier relatives develop type 2 diabetes or gestational diabetes in adulthood without any evidence of having had NDM, as well as in a small fraction of patients with early‐onset, non‐obese, and non‐autoimmune diabetes without a history of NDM. This suggests significant variability in phenotype, possibly related to other genetic or epigenetic factors that may influence the clinical expression alterations of chromosome 6q24 …”
Section: Ndm Diabetes Diagnosed Within the First 6 To 12 Months Of Lifementioning
confidence: 99%
“…This suggests significant variability in phenotype, possibly related to other genetic or epigenetic factors that may influence the clinical expression alterations of chromosome 6q24. 36,56 The role of genetic counseling depends on the underlying molecular mechanism. Uniparental disomy of chromosome 6 is generally sporadic and therefore the risk of recurrence in siblings and offspring is low.…”
Section: Transient Neonatal Diabetes From Imprinting Anomalies On 6q24mentioning
confidence: 99%
“…It has been reported that the loss of 6q24 methylation can also cause early-onset, non-obese, non-autoimmune diabetes mellitus; in this situation, being small for gestational age appears to be an essential marker [6,7]. It has been reported that the loss of 6q24 methylation can also cause early-onset, non-obese, non-autoimmune diabetes mellitus; in this situation, being small for gestational age appears to be an essential marker [6,7].…”
Section: Discussionmentioning
confidence: 99%
“…This case expands the clinical features of neonatal diabetes, especially 6q24 methylation defects. It has been reported that the loss of 6q24 methylation can also cause early-onset, non-obese, non-autoimmune diabetes mellitus; in this situation, being small for gestational age appears to be an essential marker [6,7]. Clinical hypoglycaemia was observed after diabetes remission in some people with 6q24 transient neonatal diabetes mellitus [8,9].…”
Section: Discussionmentioning
confidence: 99%
“…The hyperglycemia in these cases is often identified within the first few days of life and resolves spontaneously within the first year of life, but it returns later, usually around adolescence. However, two atypical cases of 6q24-related diabetes have recently been reported, including a case of permanent diabetes (still insulin-requiring at age 5.5 years) [5] and a case that did not have hyperglycemia during the infancy period [6]. Insulin is frequently used, although non-insulin therapies, particularly sulfonylureas, have been beneficial in some cases [79].…”
Section: Q24: Transient Congenital Diabetes Related To Over-expressimentioning
confidence: 99%